2016
DOI: 10.20546/ijcmas.2016.507.006
|View full text |Cite
|
Sign up to set email alerts
|

A study of Identification and Antifungal Susceptibility Pattern of Candida species Isolated from Various Clinical Specimens in a Tertiary care Teaching Hospital, Chinakakani, Guntur, Andhra Pradesh, South India

Abstract: The global incidence of Candidiasis has risen steadily over the past few decades. Candida species are now among the most common health care -associated pathogens. Most of the studies show that the predominant species C. albicans has been replaced by non albicans Candida with the use of antifungal agents. As various species differ in susceptibility pattern to the newer antifungal agents, antifungal susceptibility test should be performed before administration of antifungal agents. To isolate and identify differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…Shaik N et al, Gupta S and Malhotra S, have also reported sensitivity of Candida species to fluconazole ranging from 63.3% to 95%. 16,13,12 The sensitivity to Voriconazole as recorded by these authors was in the range of 76.6% to 100%. Similar results for fluconazole and voriconazole sensitivity have also been obtained by Padawer D et al from Israel, Alkilani AA et al from Egypt and Khadke S et al from Nepal.…”
Section: Resultsmentioning
confidence: 81%
“…Shaik N et al, Gupta S and Malhotra S, have also reported sensitivity of Candida species to fluconazole ranging from 63.3% to 95%. 16,13,12 The sensitivity to Voriconazole as recorded by these authors was in the range of 76.6% to 100%. Similar results for fluconazole and voriconazole sensitivity have also been obtained by Padawer D et al from Israel, Alkilani AA et al from Egypt and Khadke S et al from Nepal.…”
Section: Resultsmentioning
confidence: 81%
“…20 Also, another study from North-East India reported greater number of isolation of candida from males 62% in a study group that included patients from ICU. 21 In the present study, however, 60% of strains were isolated from females.…”
Section: Discussionmentioning
confidence: 95%
“…Plates were incubated at 25 o C for 3 -5 days following which morphological features like hyphae, pseudohyphae, blastospores and chlamydospores formation of various candida species was observed microscopically for differentiation of Candida albicans from non-albicans candida species. 20 Germ tube Test, Sugar Fermentation Tests (glucose, lactose, maltose and sucrose) and Sugar Assimilation Test was done as confirmatory tests for characterisation and identification of candida species against panel of sugars. 19 Antifungal Susceptibility Testing by Kirby-Bauer disc diffusion method was done using Mueller-Hinton agar, 2% glucose and (0.5 μg/mL) methylene blue dye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, fungal infections have become more common; additionally, there is a rising number of diseases among the immunosuppressed patients especially caused by many species of the Candida , Aspergillus , or Fusarium genera (Chakrabarti & Shivaprakash, ; Low & Rotstein, ; Shaik, Penmetcha, Myneni, Yarlagadda, & Singamsetty, ). The main risk of Candida infection encompasses a therapy with drugs that can weaken the natural microflora (Douglas, ).…”
Section: Introductionmentioning
confidence: 99%